Moho complexity in Southern California revealed by local PmP and teleseismic Ps waves - Li, Tianjue (2022)
The Moho discontinuity plays an important role in crustal growth and evolution. In this study, we delineate the Moho geometry in southern California by jointly using local Moho-reflected waves PmP and teleseismic Moho-converted waves Ps. To well constrain the Moho geometry, we have developed a two-stage process to pick PmP waves and have created a reliable PmP travel time data set with a total of 10,192 picks. We have also extracted 38,648 high-quality P-wave receiver functions (RFs). The Moho depth is initially estimated via the common conversion point (CCP) stacking of RFs and then refined by inverting the PmP travel time data in a community velocity model (CVM-H, version 15.1.1). The newly built Moho geometry is generally consistent with the California Moho Model version 1.0 (CMM-1.0), that is, a shallow Moho beneath the Salton Trough (23 km), a uniformly shallow Moho beneath the Mojave Desert and the Basin and Range (<29 km), and a sliver of deep Moho under the western Peninsular Ranges, the eastern Transverse Ranges, and the western Sierra Nevada (>34 km). However, our Moho model reveals some new features different from the CMM–1.0, such as a deep Moho (∼34 km) beneath the northern end of the central and western Transverse Ranges, consistent with the observation of deep seismicities due to a thick brittle crust there. We also find a gradual transition from the lower crust to the uppermost mantle beneath the western Peninsular Ranges, leading to the rareness of pickable PmP waves as well as weak Moho-converted signals there.